Assessment of soil quality of coastal shrimp culture pond at Chakaria, Coxs Bazar - Islam, M Shafiqul; Tarek, Mahmodul Hasan; Bhuyan, Md Simul; Zamal, Hossain (Journal of the Asiatic Society of Bangladesh, Science, 2016)
The present study was carried out to find the status of different soil quality variables of coastal shrimp culture pond at different tidal marks of Chakaria, CoxBazar during the period from August 2012 to July 2013. The values of different soil quality variables such as sand, silt, clay, pH, organic matter, NO2-N, PO4-P, exchangeable K+, Soil compactness, bulk density, particle density, porosity and Field water capacity fluctuated between 2.04-43.88%, 30.80-55.36%, 23.98-49.94%, 5.9-8.9, 1.62-9.95%, 4.01-9.92 ?g/Kg, 1.14-3.50 ?g/Kg, 0.82-1.74 meq/100g, 14.00-31.5 cm, 0.80-1.21 gcm-3, 2.11-2.74 gcm-3, 52.7-65.97% and 44.27-78.18% respectively. Significant differences (p<0.05) in the values of sand, silt, clay, bulk density, porosity, NO2-N and field water capacity of soil of the culture ponds at tide marks were observed. Strong correlations between soil bulk density vs sand (0.863), field water capacity vs clay (0.845), field water capacity vs silt (0.797), exchangeable K+ vs PO4-P (0.787), porosity vs field water capacity (0.769) and porosity vs clay (0.705) were found at 0.01% level of significance. J. Asiat. Soc. Bangladesh, Sci. 42(1): 21-27, June 2016